2017
DOI: 10.1021/acs.energyfuels.7b00958
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetic Characteristics and Model of Methane Hydrate Formation in Porous Media

Abstract: Most of the natural gas hydrates on Earth are buried in shallow formations under deep water. Comprehensively understanding the reaction kinetic characteristics of gas hydrate in porous media is very beneficial to the deep exploration of the hydrate accumulation in nature. In this paper, the formation process of CH4 hydrate in porous media was simulated physically, using a reactor that is operating at high pressure and low temperature. The hydrate phase equilibrium and reaction kinetic characteristics at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…They considered the capillary effect in the gas phase, hydrate phase, and gas phase and hydrate phase, and the results showed that the phase equilibrium curve shifted to the right by 3−8 °C when only the capillary effect on the gas phase was considered (Figure 14B), the phase equilibrium curve shifted to the left by 1−5 °C when only the capillary effect on the hydrate phase was considered (Figure 14A), and the phase equilibrium curve shifted to the right by 1−6 °C when the combined effect of the capillary effect on the two phases was considered (Figure 14C). Zhang et al 60 argued that her data supported Liu and Fleming's 116 views that the presence of porous media can induce more relaxed conditions of hydrate formation.…”
Section: ■ Effect Of Particle Size On Water-to-hydrate Conversionmentioning
confidence: 74%
See 3 more Smart Citations
“…They considered the capillary effect in the gas phase, hydrate phase, and gas phase and hydrate phase, and the results showed that the phase equilibrium curve shifted to the right by 3−8 °C when only the capillary effect on the gas phase was considered (Figure 14B), the phase equilibrium curve shifted to the left by 1−5 °C when only the capillary effect on the hydrate phase was considered (Figure 14A), and the phase equilibrium curve shifted to the right by 1−6 °C when the combined effect of the capillary effect on the two phases was considered (Figure 14C). Zhang et al 60 argued that her data supported Liu and Fleming's 116 views that the presence of porous media can induce more relaxed conditions of hydrate formation.…”
Section: ■ Effect Of Particle Size On Water-to-hydrate Conversionmentioning
confidence: 74%
“…As a result, methane gas has difficulty migrating to the bottom of the sand bed, which hinders the conversion of water to hydrate. Kumar et al 59 and Zhang et al 60 conducted similar experiments with silica sand and clay, and the results showed that a higher water conversion rate was only observed in the experiment with larger sand, while a lower water conversion rate was observed in the experiment with smaller sand and high clay content. Adeyemo et al 96 used silica gel to prove this conclusion.…”
Section: ■ Effect Of Particle Size On Water-to-hydrate Conversionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hoffrichter et al, in [7], developed a narrow FC prototype locomotive, achieving about 10% and 40% for vehicle and FC system efficiency. Zang et al, in [8], experimentally tested a fuel cell/battery/supercapacitor train, consuming almost 1.5 kg of hydrogen for 1-hour drive cycle.…”
Section: Introductionmentioning
confidence: 99%